The Effect of Fermentation Time on the Physicochemical and Microbiological Qualities of Buffalo Colostrum Kefir - Rizqiati, Heni; Nurwantoro, Nurwantoro; Prayitno, Edi; Muttaqin, Izza Wildani; Pangestu, Ridho (Journal of Applied Food Technology, 2023)
This research aims to determine the best fermentation time to produce optimal buffalo colostrum kefir. Different fermentation times at 12, 24, 36, and 48 hours were used to measure the physicochemical and microbiological characteristics of buffalo colostrum kefir. To produce buffalo colostrum kefir, fermentation process at room temperature (27˚C±1) was used. Viscosity was measured using Ostwald viscometer and Total Dissolved Solid (TDS) was measured digital refractometer. Titratable acidity was analyzed using titration method and pH value was measured using pH meter. Protein content was analyzed using Kjeldahl method and fat content was analyzed using Soxhlet method. The result shows no significant differences (P>0.05) in viscosity which results in a value of 0.92±0.09 to 0.80±0.04 cP. Meanwhile, it shows significant differences (P<0.05) on TDS (24.02±0.80 to 13.30±0.76 ºBrix), titrable acid (1.96±0.10 to 2.53±0.04%), pH value (3.95±0.03 to 3.37±0.04), protein content (14.41±0.94 to 10.57±0.68%), fat content (20.33±0.88 to 6.89±0.90%), total LAB (2.85x106 to 9.57x106 CFU/ml), total yeast (2.16x105 to 7.76x105 CFU/ml), and total microbes (5.15x106 to 5.21x106 CFU/ml). The best treatment was 36 hours of fermentation with 20% grain concentration (w/v) because it produced the highest total Lactic Acid Bacteria (LAB), total yeast, and total microbes so it is potential to be a probiotic drink.